Effects of a Protein Kinase Inhibitor on Sperm Motility in the Japanese Quail - Matsuzaki, Mei (J Poult Sci, 2017)
Sperm motility is an essential trait for successful fertilization in animals. In birds, ejaculated sperm migrate into sperm storage tubules before fertilization and are stored in a quiescent state. We previously reported that this type of sperm's flagellar quiescence was induced by lactic acid through flagellar dynein ATPase inactivation following cytoplasmic acidification (<pH 6.0). However, signal transduction in the sperm cells leading to motility inactivation is not well understood. The aim of the present study was to investigate the role of protein kinases in putative signal transduction in quail spermatozoa motility in vitro. Following incubation with bisindolylmaleimide II (BisII), a potent-competitive protein kinase C (PKC) inhibitor, sperm motility decreased in a dose related-manner. However, no such inhibitory effect was found in sperm exposed to bisindolylmaleimide V, H-89, or LY294002, a weak inhibitor of PKC, a potent inhibitor of protein kinase A (PKA) and a selective inhibitor of phosphatidylinositol 3-kinase, respectively. BisII-treated sperm exhibited no significant differences in pH(i), [Ca(2+)](i), mitochondrial activity, intracellular cAMP or ATP concentration, as well as dynein ATPase activity, compared to the control sperm. However, when the phosphorylated substrate proteins by PKC were detected by Western blot analysis, the intensity of the band in sperm incubated in the presence of BisII decreased. Moreover, immunoreactive PKCι and µ isoforms in the sperm lysates were also detected. These results indicated that the PKC signaling pathway may be involved in sperm motility regulation, and protein phosphorylation by PKC may be required to maintain flagellar movement in the Japanese quail.